The complementary of low taxes and pro-social guidelines when polluters have moral preferences - Caffera, Marcelo (2025)
Funding for this study came from Agencia Nacional de Investigación e Innovación (ANII), grants FCE_1_2019_1_156336 and POS_FCE_2020_1_1009209. Chávez acknowledges partial funding by ANID/FONDAP/1523A0007 and project Fondecyt Regular 1230266.